Progress of the acyl-Coenzyme A thioester hydrolase family in cancer - Bai, Lu; Yang, Pengjie; Han, Bater; Kong, Linghui (Frontiers in Oncology, 2024)
In recent years, the acyl-Coenzyme A thioester hydrolase family (ACOTs) has received wide attention as a key link in lipid metabolism. This family is a class of enzymes that catalyze the hydrolysis of fatty acyl-Coenzyme A, disrupting the thioester bond present within acyl-CoA ester molecules to produce free fatty acids (FFA) and the corresponding coenzyme A (CoA). Such enzymes play a very important role in lipid metabolism through maintaining appropriate levels of intracellular FFA and fatty acyl-CoA as well as CoA. It is broadly divided into two distinct subgroups, the type-I α/β-hydrolase fold enzyme superfamily and the type-II 'hot dog' fold superfamily. There are currently four human type-I genes and eight human type-II genes. Although the two subgroups catalyze the same reaction, they are not structurally similar, do not share the same sequence homology, and differ greatly in protein executive functions. This review summarizes the classification of the acyl-CoA thioester hydrolase family, an overview of the structural sequences, and advances in digestive, respiratory, and urinary systemic tumors. In order to explore potential specific drug targets and effective interventions, to provide new strategies for tumor prevention and treatment.